Description of a novel KIR3DL1*0050104 allele identified using sequence-based techniques - Yindom, L; Wang, L; Dong, T; Rowland-Jones, S (2014)
KIR3DL1*0050104 allele differs from KIR3DL1*0050101 at nucleotide positions 6709C>T (intron 5) and 11365A>G (intron 6). © 2014 John Wiley and Sons A/S.